Analysis of risk factors for T. brucei rhodesiense sleeping sickness within villages in south-east Uganda - Zoller, T.; Fèvre, Eric M.; Welburn, S.C.; Odiit, M.; Coleman, P.G. (Springer, 2008)
Sleeping sickness (HAT) caused byT.b. rhodesienseis a major veterinary and human public health problem in Uganda. Previous studies have investigated spatial risk factors forT.b. rhodesienseat large geographic scales, but none have properly investigated such risk factors at small scales, i.e. within affected villages. In the present work, we use a case-control methodology to analyse both behavioural and spatial risk factors for HAT in an endemic area.The present study investigates behavioural and occupational risk factors for infection with HAT within villages using a questionnaire-based case-control study conducted in 17 villages endemic for HAT in SE Uganda, and spatial risk factors in 4 high risk villages. For the spatial analysis, the location of homesteads with one or more cases of HAT up to three years prior to the beginning of the study was compared to all non-case homesteads. Analysing spatial associations with respect to irregularly shaped geographical objects required the development of a new approach to geographical analysis in combination with a logistic regression model.The study was able to identify, among other behavioural risk factors, having a family member with a history of HAT (p = 0.001) as well as proximity of a homestead to a nearby wetland area (p < 0.001) as strong risk factors for infection. The novel method of analysing complex spatial interactions used in the study can be applied to a range of other diseases.Spatial risk factors for HAT are maintained across geographical scales; this consistency is useful in the design of decision support tools for intervention and prevention of the disease. Familial aggregation of cases was confirmed forT. b. rhodesienseHAT in the study and probably results from shared behavioural and spatial risk factors amongmembers of a household.